Chromosomes of gaur cross domestic cattle hybrids - Bongso, T.A.; Hilmi, M.; Sopian, M.; Zulkifli, S. (1988)
The chromosomes of five gaur (Bos gaurus hubbacki) domestic cattle (B indicus cross B taurus) hybrids (three females, two males) were studied using the leucocyte culture method and centromeric (C) banding technique. All the hybrids had a diploid chromosome number of 2n = 58, made up of two submetacentric autosomes (different in size) and 54 acrocentric autosomes, most of which could be arranged in pairs in descending order of size. The sex (X) chromosomes in females were a pair of submetacentric chromosomes smaller than the submetacentric autosomes. The Y chromosome in males was a small submetacentric chromosome. The C banding patterns were useful in identifying the X and Y chromosomes and the inherited submetacentric autosomes from the gaur sire. Phenotypically, the hybrids resembled normal B indicus cross B taurus calves except for the presence of a distinct hump-like dorsal ridge containing the spinous processes of the third to 11th thoracic vertebrae, upright 'deer-like' ears and long lean legs. The potential of these hybrids as important genetic resources for meat production is stressed.